Comparison of 3 ml vs. 5 ml Local Injection of Lignocaine in Closed Reduction of Colles’ Fracture: Kashif Mahmood Khan, Ranjeet Kumar, Vinod Kumar, Muhammad Saeed Minhas, Anisuddin Bhatti (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To compare the efficacy of 3 ml vs. 5 ml lignocaine given locally in closed reduction of Colles’ fracture.Methods: Prospective randomized control trial was performed from July 2015 to December 2015. Patients older than 40 years, Colles’ fracture and fracture less than 5 days duration were included. Patients with intra articular fracture, open fracture, co-morbidities were excluded. Patients were divided equally into 2 groups, A and B by blocked randomization. Each group was injected with 1% 3 ml and 5 ml of local anesthetic lignocaine respectively. Standard hematoma block technique for Colles’ fracture was used. Efficacy was measured by pain relief at the time of manipulation using visual analogue pain scale and recorded on proforma. The data was then analyzed using SPSS software version 16.Results: 100 patients, 50 in each group were selected. In Group A patients, 05 (10%) patients had visual analogue scale (VAS) average of 2±1, while 45 (90%) patients had visual analogue scale (VAS) average of 5±1, thus non satisfactory pain control. In Group B patients, 47(94%) patients had visual analogue scale average of 1±1, while 03 (06%) patients had visual analogue scale average of 5±1, thus a satisfactory pain control.Conclusion: 5 ml of local anesthetic lignocaine used as hematoma block at fracture site provides adequate analgesia, sufficient enough for close manipulation and reduction of Colles’ fracture.Key words: Colles’ fracture, hematoma block, local anesthetic, closed manipulation